Reclaiming Indonesia’s higher education: From human capital to epistemic sustainability - Nadhira Asiyah Arrin (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: Discussions about the global education paradigm are synonymous with freedom of competition and accountability. This contrasts with the Indonesian education paradigm, which focuses on the concept of harmony between intellectual and moral development. To achieve a balance between the two paradigms, Indonesia’s Merdeka Belajar–Kampus Merdeka (MBKM) reform was launched to promote autonomy, creativity, and innovation in higher education. Yet, beneath its emancipatory discourse, MBKM remains anchored in a human-capital paradigm that measures success through employability rather than moral, ecological, and epistemic reflection. This imbalance reflects a broader crisis in modern education, where freedom is equated with market adaptability instead of ethical responsibility. Methods: This study employs a qualitative conceptual approach, combining critical discourse analysis of MBKM policy documents with theoretical synthesis across decolonial, ecological, and educational thought. The analysis proceeds through three interpretive stages—policy examination, literature synthesis, and theoretical engagement—to uncover the epistemological foundations and